Anti-Cancer and Anti-Inflammatory Activities of Three New Chromone Derivatives from the Marine-Derived Penicillium citrinum - Yi-Cheng Chu; Chun-Hao Chang; Hsiang-Ruei Liao; Shu-Ling Fu; Jih-Jung Chen (Marine Drugs, 2021)
Three new and uncommon chromone analogs, epiremisporine F (1), epiremisporine G (2), and epiremisporine H (3), were isolated from marine-origin Penicillium citrinum. Among the isolated compounds, compounds 2–3 remarkably suppressed fMLP-induced superoxide anion generation by human neutrophils, with IC50 values of 31.68 ± 2.53, and 33.52 ± 0.42 μM, respectively. Compound 3 exhibited cytotoxic activities against human colon carcinoma (HT-29) and non-small lung cancer cell (A549) with IC50 values of 21.17 ± 4.89 and 31.43 ± 3.01 μM, respectively, and Western blot assay confirmed that compound 3 obviously induced apoptosis of HT-29 cells, via Bcl-2, Bax, and caspase 3 signaling cascades.